Freebies and good governance - Singh, Balmiki Prasad (2016)
While freebies are considered among the surest and fastest means of providing succor to the needy poor, these come at a heavy cost to the national exchequer, as precious economic resources have to be diverted from developmental projects, especially those linked to infrastructure projects. An important aspect of freebies relates to a phenomenon where some communities receive better access to these than others. The communities that are better recipients of these freebies are those whose local leaders have good rapport with their representatives and administration. The promise of offering freebies to people by political parties, if they are voted to power, is now a common feature during elections in India. To usher in good governance, the twin national goals of building strong economy and to reach its benefits to the last man need to be pursued in harmony and with imagination. - Reproduced.
Keywords: Good governance; Public administration